Knowledge Sharing and Motivation Improve Librarians' Performance? - Basalamah , Salim; Mas’ud , Masdar; Sukmawati , Sukmawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study explores the influence of knowledge sharing and motivation on the performance of librarians in academic and public library settings. In the digital era, libraries are expected to deliver high-quality and innovative services, which require not only technical competence but also effective collaboration and personal drive. Knowledge sharing enables librarians to exchange expertise, enhance problem-solving abilities, and foster a culture of continuous improvement. Meanwhile, motivation—both intrinsic and extrinsic—plays a crucial role in increasing job satisfaction, commitment, and productivity. Based on a review of relevant literature and theoretical frameworks in human resource management, this paper argues that the synergy between knowledge sharing and motivation significantly contributes to enhanced librarian performance. The findings highlight the importance of organizational support in creating a conducive environment for open communication and motivational development. Implications for library management and future research directions are also discussed